Financial Regulation and Government Revenue : The Effects of a Policy Change in Ethiopia - Limodio, Nicola; Strobbe, Francesco (World Bank, Washington, DC, 2016)
Financial regulation affects government revenue whenever it imposes both the mandatory quantity and price of government bonds. This paper studies a banking regulation adopted by the National Bank of Ethiopia in April 2011, which forces all private banks to purchase a fixed negative-yield government bond in proportion to private sector lending. Having access to monthly bank balance sheets, a survey of branch costs and public finances documentation, the effect of the policy on government revenue can be tracked. This is compared to three plausible revenue-generating alternatives: raising funds at competitive rates on international markets; distorting the private lending of the state-owned bank; and raising new deposits through additional branches of the state-owned bank. Three main results emerge: the government revenue gain is moderate (1.5-2.6 percent of the tax revenue); banks comply with the policy and amass more safe assets; banks' profit growth slows without turning negative (from 10 percent to 2 percent).